Assessing completeness of a WEB site from quality perspective - Sasi Bhanu Jammalamadaka; Kamesh DBK; Jammalamadaka Kodanda Rama Sastry (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Assessing quality of a web site is most important especially because people world over are dependent on the content hosted on the WEB site for various purposes. May factors are to be considered for assessing the quality. Quality of every factor must be considered individual and also the total quality of the WEB site must be computed. This paper is primarily focused on the factor called “Completeness” which is one of the factors that can be considered for computing the quality of the WEB sites.  There can be much of the disconnected in the content hosted on the web site such as missing href, columns in the tables and forms. The more of the disconnectedness in the content that is hosted on the WEB site, the less the quality, as the information hosted on the WEB site is incomplete and less readable